Dinosaur highway : a history of Dinosaur Valley State Park - Jasinski, Laurie E. (Chisholm Trail series., 2008)
Where the Paluxy River now winds through the North Texas Hill Country, the great lizards of prehistory once roamed, leaving their impressive footprints deep in the limy sludge of what would become the earth's Cretaceous layer. It wouldn't be until a summer day in1909, however, when young George Adams went splashing along the creekbed, that chance and shifting sediments would reveal these stony traces of an ancient past. Young Adams's first discovery of dinosaur tracks in the Paluxy River Valley, near the small community of Glen Rose, Texas, came more than one hundred million years after the rei.